The Crystal Structure of Gurmarin, a Sweet Taste–Suppressing Protein: Identification of the Amino Acid Residues Essential for Inhibition. (18th August 2018) - Sigoillot, Maud; Brockhoff, Anne; Neiers, Fabrice; Poirier, Nicolas; Belloir, Christine; Legrand, Pierre; Charron, Christophe; Roblin, Pierre; Meyerhof, Wolfgang; Briand, Loïc
Abstract: Gurmarin is a highly specific sweet taste–suppressing protein in rodents that is isolated from the Indian plant Gymnema sylvestre . Gurmarin consists of 35 amino acid residues containing 3 intramolecular disulfide bridges that form a cystine knot. Here, we report the crystal structure of gurmarin at a 1.45 Å resolution and compare it with previously reported nuclear magnetic resonance solution structures. The atomic structure at this resolution allowed us to identify a very flexible region consisting of hydrophobic residues. Some of these amino acid residues had been identified as a putative binding site for the rat sweet taste receptor in a previous study. By combining alanine-scanning mutagenesis of the gurmarin molecule and a functional cell-based receptor assay, we confirmed that some single point mutations in these positions drastically affect sweet taste receptor inhibition by gurmarin.